A COMPUTER-BASED STANDARDIZED TESTING: ITS CHALLENGES AND STRATEGIES - Sulastri, Sri; Puspawati, Indah (Journal of Foreign Language Teaching and Learning, 2019)
Computer-based standardized testing has become a new way to measure students? achievement to graduate from senior high school in Indonesia, starting from 2015. Seeing the importance of this computer-based test for students, the researchers found it important to conduct a study about students? voices in this test to ensure the effective use of the test. This study focused on exploring challenges faced by the students in using a standardized-computer-based test. Moreover, the researchers also explored strategies used by the students to overcome the challenges. This study used qualitative research conducted in the English education department of a private university in Indonesia. The researchers applied an interview to six students less than one year after they conducted computer-based testing. The findings showed that insufficient facilities to conduct the test, examination?s schedule, time management, and lack of simulation were the challenges faced by the students in implementing the test. The study also revealed three strategies used by the students to overcome the challenges. There are strategies to face the challenges related to facilities, strategies to manage time better, and strategies to prepare the examination well.